2017
DOI: 10.1007/s13361-017-1708-x
|View full text |Cite
|
Sign up to set email alerts
|

Fast Determination of Ingredients in Solid Pharmaceuticals by Microwave-Enhanced In-Source Decay of Microwave Plasma Torch Mass Spectrometry

Abstract: Rapid qualitative and quantitative analysis of solid samples (e.g., pharmaceutical preparations) by using a small and low-resolution mass spectrometer without MS/MS function is still a challenge in ambient pressure ionization mass spectrometric analysis. Herein, a practically efficient method termed microwave-enhanced in-source decay (MEISD) using microwave plasma torch desorption ionization coupled with time-of-flight mass spectrometry (MPTDI-TOF MS) was developed for fast analysis of pharmaceutical tablets u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Advanced instruments increase the cost of ambient mass spectrometry and limit the spread of its application. Recently, full scan mass spectrum of pharmaceutical preparations was recorded under soft ionization conditions while only characteristic fragments were obtained under highly energetic ionization conditions using a simple time‐of‐flight mass spectrometer . Such studies indicated that the requirements of ambient mass spectrometry analysis for advanced instruments could be satisfied at a reasonable degree by tuning the energy deliverable for the ionization purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced instruments increase the cost of ambient mass spectrometry and limit the spread of its application. Recently, full scan mass spectrum of pharmaceutical preparations was recorded under soft ionization conditions while only characteristic fragments were obtained under highly energetic ionization conditions using a simple time‐of‐flight mass spectrometer . Such studies indicated that the requirements of ambient mass spectrometry analysis for advanced instruments could be satisfied at a reasonable degree by tuning the energy deliverable for the ionization purpose.…”
Section: Introductionmentioning
confidence: 99%
“…We further studied the molecular and fragmentation information of arsine under the action of the MPT which, as an efficient ambient ionization source, was applied to As analysis for the first time. 32 It can be seen from Fig. 3A that arsine exhibited a characteristic mass spectrum signal at m / z 204 in negative ion mode.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, total inorganic As (iAs(III) + iAs(V)) could be determined aer reduction under the same pH conditions as those of As(III) analysis. Consequently, iAs(V) could be calculated by the subtraction of total inorganic As and iAs(III).We further studied the molecular and fragmentation information of arsine under the action of the MPT which, as an efficient ambient ionization source, was applied to As analysis for the rst time 32. It can be seen from Fig.3Athat arsine exhibited a characteristic mass spectrum signal at m/z 204 in negative ion mode.…”
mentioning
confidence: 99%
“…Three samples (nicotinic acid, caffeine, acetaminophen) were discussed primarily. Nicotinic acid, caffeine, and acetaminophen have high proton affinity and contains high PA of nitrogen atoms (PA of nicotinic acid and caffeine are 907, 916 kJ/mol, respectively, higher than that of H 2 O, (H 2 O) 2 ; PA of acetaminophen is unknown but mainly formed protonated molecular ions). Proton-transfer reactions would occur between these samples with PWCs ions.…”
Section: Resultsmentioning
confidence: 99%
“…Before sample testing, it is expected the chemical compounds intrinsically have high ionization efficiency and low fragmentation degree to accurately and intensively represent the signal intensity changes as a function of distance L. Three samples (nicotinic acid, caffeine, acetaminophen) were discussed primarily. Nicotinic acid, caffeine, and acetaminophen have high proton affinity and contains high PA of nitrogen atoms 57 (PA of nicotinic acid and caffeine are 907, 58 916 kJ/mol, 59 respectively, higher than that of H 2 O, (H 2 O) 2 ; PA of acetaminophen is unknown but mainly formed protonated molecular ions 60 ). Proton-transfer reactions would occur between these samples with PWCs ions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%